2022
DOI: 10.1242/dev.200450
|View full text |Cite
|
Sign up to set email alerts
|

Dhx38 is required for the maintenance and differentiation of erythro-myeloid progenitors and hematopoietic stem cells by alternative splicing

Abstract: Mutations that occur in RNA splicing machinery may contribute to hematopoietic-related diseases. How splicing factor mutants perturb hematopoiesis, especially in the erythro-myeloid progenitors (EMP) process, remains elusive. Dhx38, a pre-mRNA splicing-related DEAH box RNA helicase, whose physiological function and splicing mechanisms during hematopoiesis currently remain unclear. Here we present that Dhx38 exerts a broad effect on definitive EMPs as well as the differentiation and maintenance of hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“… 41 , 42 Our previous study reported that deletion Dhx38 in zebrafish hematopoietic tissues results in DNA damage and mitotic defects due to the abnormal alternative splicing of specific genes. 11 Here, we found that DNA damage caused by DHX38 deletion in human cells and zebrafish RPCs is mainly due to the replication stress caused by R-loop accumulation. Interestingly, we also found that the abnormal R-loop accumulation was not involved in mitotic defects, suggesting that there may be other mechanisms regulating mitosis.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“… 41 , 42 Our previous study reported that deletion Dhx38 in zebrafish hematopoietic tissues results in DNA damage and mitotic defects due to the abnormal alternative splicing of specific genes. 11 Here, we found that DNA damage caused by DHX38 deletion in human cells and zebrafish RPCs is mainly due to the replication stress caused by R-loop accumulation. Interestingly, we also found that the abnormal R-loop accumulation was not involved in mitotic defects, suggesting that there may be other mechanisms regulating mitosis.…”
Section: Discussionmentioning
confidence: 77%
“…Next, to determine whether dhx38 deletion has an impact on the development of the zebrafish retina, we explored this question with a zebrafish dhx38 loss-of-function mutant. 11 We found that dhx38 homozygous mutants showed pronounced developmental defects at 36 h postfertilization (hpf) and 48 hpf, including a smaller head, abnormal eye development, and a curled-tail ( Figures 1 A–1C), and died at 3–4 days post fertilization (dpf). The detailed retinal phenotypes of dhx38 knockout zebrafish were observed using immunofluorescence and WISH assays with the corresponding antibodies and probes.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Dhx38 contributes to the differentiation of hematopoietic stem cells, which can develop into various types of blood cells. 70 One TF, Sall4, is also included in this cluster and it regulates genes that initiate hematopoiesis, contributing to the activation of the blood-specific program in zebrafish embryos. 71 Sall4 also modulates the development of pectoral fin and taste epithelia in zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…The seven upregulated RNA helicases including Hells, Ddx39a, Ddx19b, Dhx38, Ddx3, Ddx5, and Chd7, play essential roles in promoting transcription, cellular differentiation, and early organogenesis. 55 , 56 , 64 , 65 , 66 , 68 , 69 , 70 , 112 …”
Section: Resultsmentioning
confidence: 99%